2015
DOI: 10.14202/vetworld.2015.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter species in milk and milk products, their virulence gene profile and antibiogram

Abstract: Aim:During the last decades, number of food poisoning cases due to Campylobacter occurred, immensely. After poultry, raw milk acts as a second main source of Campylobacter. Therefore, the present study was undertaken to detect the prevalence of Campylobacters in milk and milk products and to know the antibiotic sensitivity and virulence gene profile of Campylobacter spp. in Anand city, Gujarat, India.Material and Methods:A total of 240 samples (85 buffalo milk, 65 cow milk, 30 cheese, 30 ice-cream and 30 panee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 50 publications
(42 reference statements)
6
41
2
Order By: Relevance
“…C. coli is frequently isolated from pork (QIN et al, 2011;GHIMIRE et al, 2014;WYSOK et al, 2015a;WYSOK et al, 2015b). Although, the lower rates were detected in raw milk and dairy products (WHYTE et al, 2004;HUSSAIN et al, 2007;BIANCHI et al, 2013;MODI et al, 2015;BERTASI et al, 2016;CHRISTIDIS et al, 2016) (2016) demonstrated a 27.3%, 20%, 17.2%, 13.4% prevalence of Campylobacter in milk samples, respectively. All this emphasizes the importance of raw milk and dairy products as a potential source of Campylobacter.…”
Section: Resultsmentioning
confidence: 99%
“…C. coli is frequently isolated from pork (QIN et al, 2011;GHIMIRE et al, 2014;WYSOK et al, 2015a;WYSOK et al, 2015b). Although, the lower rates were detected in raw milk and dairy products (WHYTE et al, 2004;HUSSAIN et al, 2007;BIANCHI et al, 2013;MODI et al, 2015;BERTASI et al, 2016;CHRISTIDIS et al, 2016) (2016) demonstrated a 27.3%, 20%, 17.2%, 13.4% prevalence of Campylobacter in milk samples, respectively. All this emphasizes the importance of raw milk and dairy products as a potential source of Campylobacter.…”
Section: Resultsmentioning
confidence: 99%
“…The Campylobacteriaceae family is divided into four genera: Campylobacter , Arcobacter , Dehalospirilum , and Sulfurospirilum [ 26 ]. Campylobacter spp.…”
Section: Campylobacteriosismentioning
confidence: 99%
“…The identified Campylobacter species were further screened for the presence of invasion genes (ciaB and iam), adherence genes (flaA and cadF), a toxin gene (cdtB) and flagella synthesis, and a modification gene (flgR). The primer sets for the detection of cdtB, flaA and cadF genes were used as reported by Modi et al [24], iam gene [42], ciaB gene [43] and flgR) gene [44].…”
Section: Molecular Detection Of Virulence Genesmentioning
confidence: 99%